A NEW PROFIT OPTIMIZATION METHOD BASED ON GENETIC ALGORITHM FOR A SAMPLE FIRM OPERATING IN ANTALYA PROVINCE (Third Sector Social Economic Review, 2018)
Logistics industry has an important position in the economic structure of the countries in terms of both production process and investment. Many provinces is a center of logistics industry in Turkey which has the potential of acquiring the position of a logistic base over the globe due to its geopolitical location and investments carried out for the logistics industry.  These centers aim to maximize their profits in order to compete with international firms and also to sustain their activities.  The main aim of this study is to enable logistics firms to maximize their profits by determining the ratio of internal factors which can be determined by themselves such as private goods and rental vehicle against external factors which can't be determined by themselves such as amount of agricultural products, number of tourists and exchange rate. Therefore, the study has been conducted specific to Antalya province which is a wide and very lively logistics center due to abundance of the agricultural products and number of tourists hosted and international events organized. And in the study, profit optimization model based on genetic algorithm was developed by using monthly data of Antalya province for the period of January 2010 and September 2017.
Keywords: Firm Behavior; Logistics Sector; Genetic Algorithm; Artificial Neural Networks; Optimization